African intimacies : race, homosexuality, and globalization - Hoad, Neville Wallace, 1966- (University of Minnesota Press, 2007)
There have been few book-length engagements with the question of sexuality in Africa, let alone African homosexuality. African Intimacies simultaneously responds to the public debate on the ÒAfricannessÓ of homosexuality and interrogates the meaningfulness of the terms ÒsexualityÓ and ÒhomosexualityÓ outside Euro-American discourse. Speculating on cultural practices interpreted by missionaries as sodomy and resistance to colonialism, Neville Hoad begins by analyzing the 1886 Bugandan martyrs incidentÑthe execution of thirty men in the royal court. Then, in a series of close readings, he addres.